The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1463-1318.2009.01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for obstructed defaecation: does the use of the Contour device (Trans‐STARR) improve results?

Abstract: Our study shows that both procedures are safe and effective in the surgical treatment of obstructed defaecation but despite a larger resection the Trans-STARR procedure does not offer any additional benefit. A policy of individualizing techniques tailored to the extent of prolapse may be appropriate, but requires further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…However, there were also some opposing views. Wadhawan et al[ 97 ] and Naldini et al[ 65 ] indicated that there were no statistically significant differences in postoperative clinical outcome, early complications, postoperative pain or hospital stay between PPH-STARR procedure and Contour-Transtar procedure. Similarly, Boccasanta et al[ 98 ] demonstrated that no improvements in symptoms and defecographic parameters were observed postoperatively in patients who underwent operation using Contour-Transtar procedure compared with PPH-STARR procedure.…”
Section: Alternative Transanal Surgical Procedures For Odsmentioning
confidence: 99%
“…However, there were also some opposing views. Wadhawan et al[ 97 ] and Naldini et al[ 65 ] indicated that there were no statistically significant differences in postoperative clinical outcome, early complications, postoperative pain or hospital stay between PPH-STARR procedure and Contour-Transtar procedure. Similarly, Boccasanta et al[ 98 ] demonstrated that no improvements in symptoms and defecographic parameters were observed postoperatively in patients who underwent operation using Contour-Transtar procedure compared with PPH-STARR procedure.…”
Section: Alternative Transanal Surgical Procedures For Odsmentioning
confidence: 99%
“…The optimal treatment of patients with combined STC and ODS is still unclear. Solely stapled transanal rectal resection (STARR) or colectomy with ileorectal anastomosis could not resolve the coexisting problems [ 1 , 7 ]. Inspired by the modified Duhamel operation, in this study we introduced a new surgical procedure, named the Jinling procedure after our hospital, to treat mixed constipation ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 However, several reports have raised doubts about the long-term success of STARR for the treatment of obstructive defecation. [6][7][8][9] In one study, Dodi et al 9 reported severe postoperative complications, including rectal bleeding, anal pain, fecal incontinence, and rectovaginal fistula, or recurrence of rectocele, rectal intussusception, or obstructed defecation symptoms, in 14 patients who underwent the STARR procedure.…”
mentioning
confidence: 98%
“…Several studies have shown that the sole use of STARR or colectomy with ileorectal anastomosis does not resolve the coexisting problems. 2,6,7 Some authors have recommended preoperative biofeedback to improve functional results after subtotal colectomy in patients with slow-transit constipation and obstructive defecation. 14 However, in a study evaluating preoperative biofeedback and subtotal colectomy in 16 patients with combined slowtransit constipation and nonrelaxing pelvic floor, Bernini et al 21 found that 37.5% of patients still complained of incomplete evacuation.…”
mentioning
confidence: 99%